ANALISIS TRANSPARANSI FISKAL TERHADAP LAPORAN BELANJA PERPAJAKAN (TAX EXPENDITURE REPORT) DI INDONESIA - Mariani Mariani; Endang Kiswara (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to determine differences in tax expenditure report before and after being updated. This research also aims to determine whether the estimated tax expenditure is in accordance with the policy objectives. This descriptive research is a form of non-hypothesis research so it does not require the formulation of a hypothesis. So, researchers only use descriptive statistical analysis methods to provide an overview of the data presented with a minimum value, maximum value, means and standard deviations. Based on the results of research that has been done, the most estimated ta expenditure is used to improve people’s welfare. In addition, there are differences in the estimated value of tax expenditure from the tax expenditure reports for 2016-2017 and 2018.